Предмет: Математика,
автор: Fromen
ПОЖАЛУЙСТА ПОМОГИТЕ! Разложите на множители выражения:
1)0,01а^2-(а-3)^2
2)(3х-2)^3+(5-4х)^3
Ответы
Автор ответа:
2
1)0,01а²-(а-3)²=(0.1а-(а-3))(0.1а+(а-3))=(3-0.9а)*(1.1а-3)
2)(3х-2)³+(5-4х)³=((3х-2)+(5-4х))((3х-2)²-(3х-2)*(5-4х)+(5-4х)²)=
(3-х)*(9х²-12х+4-(3х-2)(5х-4)+25-40х+16х²)=
(3-х)*(25х²-52х+29-(3х-2)(5х-4))=(3-х)*(25х²-52х+29-(15х²-22х+8))=
(3-х)*(10х²+30х+21)
Использовал формулы сокращенного умножения
а²-в²=(а-в)*(а+в)
а³+в³=(а+в)*(а²-ав+в²)
Fromen:
Большое спасибо
Похожие вопросы
Предмет: Биология,
автор: grigorychalov
Предмет: Математика,
автор: Ferhad2009
Предмет: История,
автор: sashaalechencov60
Предмет: Геометрия,
автор: HOBBIT111111111
Предмет: Геометрия,
автор: ushwshuws